Relação peso-comprimento e fator de condição para Cichla cf. ocellaris e Cichla monoculus (Perciformes, Cichlidae) no reservatório de Volta Grande, Rio Grande - MG/SP - Muller Gomiero, Leandro [UNESP]; De Souza Braga, Francisco Manoel [UNESP] (My University, 2003)
The aim of this paper was to analyze the length-weight relationship and the condition factor of two species of cichlids (Cichla cf. ocellaris and Cichla monoculus) (Perciformes, Cichlidae) that were inducted in Volta Grande Reservoir, Rio Grande. There was no difference in the length-weight relationship between the sexes for Cichla cf. ocellaris and Cichla monoculus. The allometric condition factor showed a fall in the spring and another smaller one in the winter. It happens when these fishes change their feeding activity. In the spring all the reproductive behavior are developed and, in the winter, there is a shortage of prey. The variation of the relative condition factor followed the variation of the allometric condition factor due to the low contribution of the gonads weight and the small amount of accumulated fat in the total weight. The length distribution, length-weight relationship and condition factor of these fishes vary in accordance with the time of introduction into the reservoir, the characteristics of the ecosystem as well as the interactions among the species at these sites.
Length-weight relationship and condition factor for Cichla cf. ocellaris and Cichla monoculus (Perciformes, Cichlidae) in Volta Grande Reservoir, Rio Grande - MG/SP
Keywords: Cichla; Condition factor; Length-weight relationship; Reservoir; Rio Grande; Brazil; community ecology; conditioning; controlled study; feeding behavior; fish; gonad; lipid storage; nonhuman; Perciformes; prey; reservoir; sexual behavior; species difference; spring; winter; Cichla monoculus; Cichla ocellaris; Cichlidae; Pisces